2010
DOI: 10.1007/s10725-010-9465-x
|View full text |Cite
|
Sign up to set email alerts
|

The roles and interactions of ethylene with gibberellins in the far-red enriched light-mediated growth of Solanum lycopersicum seedlings

Abstract: Wild type (WT) tomato seedlings responded to a low red to far-red (R/FR) ratio with increased stem elongation, similar leaflet area expansion and lower shoot ethylene levels. The levels of endogenous growth-active GA 1 and its immediate precursor GA 20 were decreased by low R/FR ratio, whereas the levels of GA 1 catabolite, GA 8 , increased. To examine the interaction of ethylene with GAs in regulating tomato shoot growth under low R/FR ratio, transgenic (T) seedlings bearing Le-ACS2 and Le-ACS4 antisense mRNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 32 publications
1
14
0
Order By: Relevance
“…Tomato could be considered in the first group. These results agreed with Kurepin et al (2010) who found wild-type tomato seedlings responded to a low R:FR ratio with increased stem elongation. UVA and UVB can produce changes in reduction of stem length (Mark and Tevini, 1996).…”
Section: Resultssupporting
confidence: 92%
“…Tomato could be considered in the first group. These results agreed with Kurepin et al (2010) who found wild-type tomato seedlings responded to a low R:FR ratio with increased stem elongation. UVA and UVB can produce changes in reduction of stem length (Mark and Tevini, 1996).…”
Section: Resultssupporting
confidence: 92%
“…Plant growth retardants (synthetic chemicals that are capable of inhibiting GA biosynthesis) have been extensively studied and are successfully used for the manipulation of agronomic crops . The majority of these chemicals are used to reduce vegetative growth (without toxicity effects) while preserving crop yield . Growth retardant treatment can also increase seed yield in perennial ryegrass plants.…”
Section: Plant Hormonesmentioning
confidence: 99%
“…This may be another approach to explain the occurrence after disbudding. Also light, and especially the R:FR, affects ethylene production: through the circadian clock (Rikin et al, 1984;Finlayson et al, 1998;Jasoni et al, 2002;Dziubinska et al, 2003;Thain et al, 2004), by production (Finlayson et al, 1998(Finlayson et al, , 1999Kurepin et al, 2007Kurepin et al, , 2010Kurepin et al, , 2011, and by sensitivity (Pierik et al, 2004).…”
Section: Involvement Of Phytohormonesmentioning
confidence: 99%